Comparative assessment of forage and livestock density in Tekeze River Basin - Bizuwork, A.; Tadddesse, G.; Sonder, Kai; Peden, Donald G.; Jobre, Y. (2006)
Agriculture is the mainstay of the country and also the major source of employment and income. About 85 percent of the population live in the rural areas and are primarily engaged in agriculture and related activities. Among the other agricultural sector, livestock production contributes about 30-35% of agricultural gross domestic product (GDP) and more than 85% of farm cash income. In this study , a comparative assessment of forage and livestock density has been undertaken in Tekeze river basin by applying GIS and remote sensing techniques. Based on the analysis, the net Primary Product (NPP) in Tekeze river basin ranges from 0.3 to 4 kg/m2/yr. About 73% of the study area has NPP value of below 2 Kg/m2/year. The rest 27% accounts 2.4 kg/m2/year. The analysis showed that the value of RUE ranges from 0.5 to 4.6 g/m2/year. The grazing pressure index (GPI) of Tekeze river basin shows that the range falls between 0 to 400 TLU/kg. The result also shows that only 35 of the total area is between 0 to 1 TLU/kg which is in the normal grazing pressure threshold. The rest 975 showed that there is over grazing in the river basin. The amount of forage available at the moment compare to the existing livestock number is inadequate.